A Mixed-Methods Study on Senior High School EFL Teacher Resilience in China - Chu, Wenxiu; Liu, Honggang (Frontiers in Psychology, 2022)
While teacher resilience has gained significant attention in recent years, the empirical exploration of this issue is still insufficient, particularly with regard to English as a foreign language (EFL) teacher resilience in China. Against this backdrop, this study employed a mixed-methods design to investigate Chinese EFL teacher resilience. Specifically, the Connor-Davidson Resilience Scale (CD-RISC)-EFL Teacher Survey (Liu & Chu, 2022) was conducted among 330 Chinese senior high school EFL teachers. Five volunteers in the sample of the survey participated in semi-structured interviews. The results revealed that resilience in Chinese senior high school EFL teachers was at a moderate to high level, and there was no significant difference of teacher resilience in terms of gender and years of teaching experience, but a slightly significant difference on teachers’ educational background. Possible reasons for interpreting EFL teacher resilience were provided from personal and contextual perspectives. Finally, implications of these findings were discussed for developing teacher resilience.